Radiation combined with macrophage depletion promotes adaptive immunity and potentiates checkpoint blockade - Keaton I Jones; Jiske Tiersma; Arseniy E Yuzhalin; Alex N Gordon‐Weeks; Jon Buzzelli; Jae Hong Im; Ruth J Muschel (EMBO Molecular Medicine)
Abstract Emerging evidence suggests a role for radiation in eliciting anti‐tumour immunity. We aimed to investigate the role of macrophages in modulating the immune response to radiation. Irradiation to murine tumours generated from colorectal (MC38) and pancreatic (KPC) cell lines induced colony‐stimulating factor 1 (CSF‐1). Coincident with the elevation in CSF‐1, macrophages increased in tumours, peaking 5 days following irradiation. These tumour‐associated macrophages (TAMs) were skewed towards an immunosuppressive phenotype. Macrophage depletion via anti‐CSF (aCSF) reduced macrophage numbers, yet only achieved tumour growth delay when combined with radiation. The tumour growth delay from aCSF after radiation was abrogated by depletion of CD8 T cells. There was enhanced recognition of tumour cell antigens by T cells isolated from irradiated tumours, consistent with increased antigen priming. The addition of anti‐PD‐L1 (aPD‐L1) resulted in improved tumour suppression and even regression in some tumours. In summary, we show that adaptive immunity induced by radiation is limited by the recruitment of highly immunosuppressive macrophages. Macrophage depletion partly reduced immunosuppression, but additional treatment with anti‐PD‐L1 was required to achieve tumour regression.